2022
DOI: 10.1126/scitranslmed.abk2709
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of METTL3 attenuates renal injury and inflammation by alleviating TAB3 m6A modifications via IGF2BP2-dependent mechanisms

Abstract: The role of N 6 -methyladenosine (m6A) modifications in renal diseases is largely unknown. Here, we characterized the role of N 6 -adenosine-methyltransferase-like 3 (METTL3), whose expression is elevated in renal tubules in different acute kidney injury (AKI) models as well as in human biopsies and cultured tubular epithelial cells (TECs). METTL3 silencing alleviated renal inflammation and programmed cell death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 51 publications
5
78
0
Order By: Relevance
“…regulate the development of multiple diseases (e.g., tumor and kidney injury) through glycan metabolism. [ 103 , 104 ], and these pathogenic mechanisms involve different signaling pathways (GLUT1-mTORC1 axis, TRAF6/NF-κB and NF-κB/MAPK pathways). For example, METTL3 promotes colorectal cancer by activating the m6A-GLUT1-mTORC1 axis [ 104 ]; YTHDF2 mediates lipopolysaccharide-induced osteoclastogenesis and inflammatory response via the NF-κB and MAPK signaling pathways [ 105 ].…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…regulate the development of multiple diseases (e.g., tumor and kidney injury) through glycan metabolism. [ 103 , 104 ], and these pathogenic mechanisms involve different signaling pathways (GLUT1-mTORC1 axis, TRAF6/NF-κB and NF-κB/MAPK pathways). For example, METTL3 promotes colorectal cancer by activating the m6A-GLUT1-mTORC1 axis [ 104 ]; YTHDF2 mediates lipopolysaccharide-induced osteoclastogenesis and inflammatory response via the NF-κB and MAPK signaling pathways [ 105 ].…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…Having demonstrated that cell cycle dysregulation is one of the pivotal mechanisms underlying GCs damages, we reasoned that a cell cycle regulating factor might be involved in this process. Previous studies have revealed that IGF2BPs, an RNA-binding protein family facilitating to stabilize its target RNAs [ [15] , [16] , [17] , [18] ], play a key role in controlling cell cycle and regulating cancer cell proliferation [ 20 , [41] , [42] , [43] ]. IGF2BPs knockdown or depletion impaired cell cycle progression and limited tumor growth [ 20 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found the treatment of 3-nitropropionic acid (3-NP), a mitochondrial toxin inducing intracellular OS by targeting complex II of electron transport chain, led to significant downregulation of Insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) and subsequently resulted in MDM2 mRNA instability in GCs. IGF2BP1 is an RNA-binding protein which preferentially binds to m 6 A modifications and helps to stabilize its targeted transcripts [ [15] , [16] , [17] , [18] ]. As a potent oncogenic factor, IGF2BP1 regulates proliferation, cell cycle progression and stemness of cancer cells [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, knockdown of METTL3 attenuated renal inflammation and programmed cell death in tubular epithelial cells. 13 Notably, our previous research revealed that significantly increased levels of METTL3 in the corneal tissue of F. solani -infected mice. 14 However, the molecular pathway and mechanism of the function of METTL3 in FK has not been well elucidated.…”
mentioning
confidence: 94%